Little evidence of adaptation potential to ocean acidification in sea urchins living in "Future Ocean" conditions at a CO2 vent. Issue 17 (18th August 2019) - Uthicke, Sven; Deshpande, Nandan P.; Liddy, Michelle; Patel, Frances; Lamare, Miles; Wilkins, Marc R.
Abstract: Ocean acidification (OA) can be detrimental to calcifying marine organisms, with stunting of invertebrate larval development one of the most consistent responses. Effects are usually measured by short‐term, within‐generation exposure, an approach that does not consider the potential for adaptation. We examined the genetic response to OA of larvae of the tropical sea urchin Echinometra sp. C. raised on coral reefs that were either influenced by CO2 vents (pH 7.9, future OA condition) or nonvent control reefs (pH 8.2). We assembled a high quality de novo transcriptome of Echinometra embryos (8 hr) and pluteus larvae (48 hr) and identified 68, 056 SNPs. We tested for outlier SNPs and functional enrichment in embryos and larvae raised from adults from the control or vent sites. Generally, highest F ST values in embryos were observed between sites (intrinsic adaptation, most representative of the gene pool in the spawned populations). This comparison also had the highest number of outlier loci (40). In the other comparisons, classical adaptation (comparing larvae with adults from the control transplanted to either the control or vent conditions) and reverse adaptation (larvae from the vent site returned to the vent or explanted at the control), we only observed modest numbers of outlier SNPs (6–19) and only enrichment in two functional pathways. Most of the outliers detected were silent substitutions without adaptive potential. We conclude that there is little evidence of realized adaptation potential during early development, while some potential (albeit relatively low) exists in the intrinsic gene pool after more than one generation of exposure. Abstract : Questions of the potential for adaptation to Ocean Acidification (OA) are often investigated in short term artificial aquarium setting. We use the unique setting of a carbon dioxide vent on a coral reef as an in‐situ test field to investigate the potential for adaptation in an ecologically important sea urchin species. We exposed offspring from adults grown at control and vent sites in a cross‐transplant experiment. Based on a transcriptome assembled de novo, we test for the potential of adaptation by testing for outlier SNPs amongst >60, 000 SNPs discovered.